Involvement of the P2X7purinergic receptor and c-Jun N-terminal and extracellular signal-regulated kinases in cyclooxygenase-2 and prostaglandin E2induction by LL-37 - Pareena Chotjumlong (2018)
Periodontal disease is caused by microorganisms and host-derived inflammation involving increased cyclooxygenase-2 (COX-2) expression and prostaglandin E2(PGE2) production. We previously demonstrated that human β-defensin-3 induces COX-2 and PGE2in human gingival fibroblasts (HGFs). We, therefore, aimed to examine the inducible effects of LL-37, the only cathelicidin expressed in humans, on COX-2 expression and PGE2synthesis in HGFs and to elucidate the relevant signaling pathways. The COX-2 expression was upregulated by LL-37 in dose- and time-dependent manners. Accordingly, the synthesis of PGE2in cell-free culture supernatants was raised by LL-37 (p < 0.01) and blocked by NS-398, a specific COX-2 inhibitor (p < 0.01). P2X inhibitors and a neutralizing antibody against P2X7purinergic receptor significantly abrogated COX-2 induction and PGE2production by LL-37 (p < 0.01). LL-37 upregulated COX-2 expression and PGE2synthesis via activation of extracellular signal-regulated kinase (ERK) and p46 c-Jun N-terminal kinase (JNK), while interleukin-1β did so via nuclear factor-κB and all three mitogen-activated protein kinases. In summary, LL-37 can control arachidonic acid metabolism by induction of COX-2 expression and PGE2synthesis via the P2X7receptor, ERK, and p46 JNK. The pro-inflammatory effects of LL-37 may be essential for initiating oral mucosal inflammation in periodontal disease. Copyright © 2012 S. Karger AG, Basel.